2015
DOI: 10.1007/s00376-015-4194-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the seasonal forecasting of the Asian summer monsoon by BCC_CSM1.1(m)

Abstract: This paper provides a comprehensive assessment of Asian summer monsoon prediction skill as a function of lead time and its relationship to sea surface temperature prediction using the seasonal hindcasts of the Beijing Climate Center Climate System Model, BCC CSM1.1(m). For the South and Southeast Asian summer monsoon, reasonable skill is found in the model's forecasting of certain aspects of monsoon climatology and spatiotemporal variability. Nevertheless, deficiencies such as significant forecast errors over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 57 publications
1
44
1
Order By: Relevance
“…The sea ice component is GFDL Sea Ice Simulator. Details on similar versions of BCC_CSM and their use in climate change projection and short-term climate prediction have been documented in several studies (e.g., Wu et al 2013Wu et al , 2014Liu et al 2014Liu et al , 2015.…”
Section: Modelmentioning
confidence: 99%
“…The sea ice component is GFDL Sea Ice Simulator. Details on similar versions of BCC_CSM and their use in climate change projection and short-term climate prediction have been documented in several studies (e.g., Wu et al 2013Wu et al , 2014Liu et al 2014Liu et al , 2015.…”
Section: Modelmentioning
confidence: 99%
“…For example, the ENSEMBLES, DEMETER, BCC_CSM1.1m, CFS and POAMA have relatively similar skill (e.g. Wang et al, ; Li et al, ; Liu et al, ) when the interannual EASM index defined by Wang and Fan () is employed. But, the prediction skill for summer precipitation over East Asia and the northwest Pacific shows differences in different models (Lee et al, ; Li et al, ), and has only recently been demonstrated in any system (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The BCC_CSM, with the inclusion of ocean-land-atmosphere-ice coupling and carbon cycle, has coarse-and moderate-resolution versions that participated in the CMIP5 and provided reasonable simulations of climate change (Wu et al 2013. Also, the BCC_CSM with a moderate resolution has been used in seasonal prediction and exhibited reliable performance (Liu et al 2014a(Liu et al , 2015a.…”
Section: Modelmentioning
confidence: 99%
“…Also, as one of the participants in the S2S Prediction Project, the BCC has conducted comprehensive S2S reforecast experiments using a coupled model since 2014. Before its participation in the S2S Project, only atmosphere-only models were used at the BCC to fulfill sub-seasonal forecast with a below-50-day integration, while coupled models were only applied in seasonal climate prediction and had reasonable skills in predicting Asian monsoon and ENSO (Liu et al 2014a(Liu et al , 2015a. Because of insufficient practical experience as well as lack of high-quality assimilation analysis, it is found that the initial S2S reforecast experiments showed limited skills in capturing sub-seasonal variability of climate phenomenon, especially the MJO.…”
Section: Introductionmentioning
confidence: 99%